I think it would be the second one
![\bf \textit{perimeter of a rectangle}=p=side+side+side+side \\\\ or\implies p=w+w+l+l\implies p=2w+2l \\\\ p=2(w+l)\qquad \begin{cases} w=width\\ l=length\\ ------\\ p=48 \end{cases}\implies 40=2(w+l)\\\\ -----------------------------\\\\ \textit{area of it}=A=w\cdot l\qquad \begin{cases} w=width\\ l=length\\ ------\\ A=40 \end{cases}\implies 40=wl\\\\ -----------------------------\\\\](https://tex.z-dn.net/?f=%5Cbf%20%5Ctextit%7Bperimeter%20of%20a%20rectangle%7D%3Dp%3Dside%2Bside%2Bside%2Bside%0A%5C%5C%5C%5C%0Aor%5Cimplies%20p%3Dw%2Bw%2Bl%2Bl%5Cimplies%20p%3D2w%2B2l%0A%5C%5C%5C%5C%0Ap%3D2%28w%2Bl%29%5Cqquad%20%0A%5Cbegin%7Bcases%7D%0Aw%3Dwidth%5C%5C%0Al%3Dlength%5C%5C%0A------%5C%5C%0Ap%3D48%0A%5Cend%7Bcases%7D%5Cimplies%2040%3D2%28w%2Bl%29%5C%5C%5C%5C%0A-----------------------------%5C%5C%5C%5C%0A%5Ctextit%7Barea%20of%20it%7D%3DA%3Dw%5Ccdot%20l%5Cqquad%20%5Cbegin%7Bcases%7D%0Aw%3Dwidth%5C%5C%0Al%3Dlength%5C%5C%0A------%5C%5C%0AA%3D40%0A%5Cend%7Bcases%7D%5Cimplies%2040%3Dwl%5C%5C%5C%5C%0A-----------------------------%5C%5C%5C%5C%20)
![\bf thus\qquad \begin{cases} 40=2(w+l)\to \frac{40}{2}=w+l\to\frac{40}{2}-l=\boxed{w} \\\\ 40=wl\\ --------------\\ 40=\left( \boxed{\frac{40}{2}-l} \right)\cdot l \end{cases}](https://tex.z-dn.net/?f=%5Cbf%20thus%5Cqquad%20%0A%5Cbegin%7Bcases%7D%0A40%3D2%28w%2Bl%29%5Cto%20%5Cfrac%7B40%7D%7B2%7D%3Dw%2Bl%5Cto%5Cfrac%7B40%7D%7B2%7D-l%3D%5Cboxed%7Bw%7D%0A%5C%5C%5C%5C%0A40%3Dwl%5C%5C%0A--------------%5C%5C%0A40%3D%5Cleft%28%20%5Cboxed%7B%5Cfrac%7B40%7D%7B2%7D-l%7D%20%5Cright%29%5Ccdot%20l%0A%5Cend%7Bcases%7D)
solve for "l" to find its length
To find percentage, you take 37.8 and divide it by 63.8 then multiply by 100
(37.8/63.8) × 100 = 59.25%
Answer:
<em>S</em><em>o</em><em> </em><em>1</em><em>)</em><em> </em><em> </em><em>x</em><em>²</em><em>-</em><em>2</em><em>x</em><em>-</em><em>8</em>
<em>=</em><em> </em><em> </em><em> </em><em> </em><em> </em> x(x-2-8/x)
<em>2</em><em>)</em><em> </em><em> </em><em> </em><em>y</em><em>²</em><em>-</em><em>1</em><em>3</em><em>y</em><em>+</em><em>4</em><em>2</em>
<em> </em><em>=</em><em> </em><em> </em><em> </em>y(y-13+42/y)
<em>3</em><em>)</em><em> </em><em>m</em><em>²</em><em>-</em><em>6</em><em>m</em><em>-</em><em>7</em>
<em> </em><em>=</em><em> </em><em>m</em><em>(</em><em>m</em><em>-</em><em>6</em><em>-</em><em>7</em><em>/</em><em>m</em><em>)</em>
<em>H</em><em>o</em><em>p</em><em>e</em><em> </em><em>i</em><em>t</em><em> </em><em>h</em><em>e</em><em>l</em><em>p</em><em>s</em>
7 = 2n - 2
n= a number so twice a number is 2n and 7 is 2 less than twice this number.